Recognition of defined epitopes by affinity-purified anti-immunoglobulin fab autoantibodies isolated from HIV-infected humans - Marchalonis, John J.; Garza, A.; Lake, D. F.; Landsperger, W. J.; Süsal, Caner (Journal of molecular recognition, 1999)
Infection of humans with HIV-1 has previously been independently shown to result in the generation of autoantibodies (AAbs) reactive with immunoglobulin Fab fragments (Heidelberg), and with autoantibodies to T-cell receptors (TCRs) (Tucson). Here, we carry out epitope mapping studies of affinity-purified AAbs to Fab fragments prepared from individual HIV-positive patients for their capacity to bind recombinant constructs and peptide-defined epitopes modeling TCR and Ig light chains. Some affinity-purified autoantibodies reacted strongly with TCRs expressed by intact T-cells, and recombinant Valpha/Vbeta constructs as well as with certain synthetic peptide epitopes. The binding reactions of affinity-purified AAbs of individual patients were distinct, and the AAb preparations consisted of populations of polyclonal lgs as reflected in specificity and isotype. AAb pools from individual patients all bound particular regions of TCR and Ig chains defined by comprehensive peptide synthesis including the CDR1 and Fr3 segments of the variable domains and the joining segment/switch peptide. In addition, other reactivities to restricted regions of alpha, beta and lambda light chains were documented. These results substantiate the cross-reactivity of TCR and Ig-Fab determinants, and are consistent with the hypothesis that autoantibodies arising as a consequence of HIV infection can have an immunomodulatory role.